Penentuan Litologi Batuan di Daerah Samboja Berdasarkan Analisis Pemodelan 3D Data Cutting dan Data Logging Geofisika - Situmeang, Edberg; Djayus, Djayus; Wahidah, Wahidah; Supriyanto, Supriyanto; Lepong, Piter (GEOSAINS KUTAI BASIN, 2023)
The interpretation of rock lithology is inaccurate if it only uses cutting data, so it must be assisted with other data, including logging data. The purpose of this study was to determine the lithological arrangement of rocks based on cutting data and logging data and to compare the cross section results of cutting data and logging data. This study uses cutting data and logging data (gamma ray log and density log). Cutting data and logging data will be interpreted and processed into 2D and 3D sections which are corrected with topographical data including coordinates, elevation values, strike dip and total depth. The results of processing from both methods, obtained lithology composition in the form of soil, silt, sand, coal, clay, carbon and carbont clay.